Savings and the Terms of Trade under Borrowing Constraints - Agenor, Pierre-Richard; Aizenman, Joshua (World Bank, Washington, DC, 2014)
The authors examine the extent to which permanent terms-of-trade shocks have an asymmetric effect on private savings. Using a simple three-period model, they show that if households expect to face binding constraints on borrowing in bad states of nature (when the economy is in a long trough rather than a sharp peak). Savings rates will respond asymmetrically to favorable movements in the permanent component of the terms of trade - in contrast with the predictions of conventional consumption-smoothing models. They test the asymmetric effects of terms-of-trade disturbances using an econometric model that controls for various standard determinants of private savings. The results - based on panel data for non-oil commodity exporters of Sub-Saharan Africa for 1980-96 (a group of countries for which movements in the terms of trade have traditionally represented a key source of macroeconomic shocks) - indicate that increases in the permanent component of the terms of trade (measured using three alternative filtering techniques) indeed tend to be associated with higher rates of private savings.